Causes and implications of the unforeseen 2016 extreme yield loss in the breadbasket of France - Tamara Ben-Ari (Nature Portfolio, 2018)
In France, the 2016 winter wheat harvest was at its lowest since over 50 years. Here, Ben-Ari et al. show the role of seasonal temperature and precipitation extremes in this loss, and accounting for both of these variables explains large, historical yield loss events.